The relationship between self-control and academic achievement: A meta-analysis investigation - Sulistio Mukti Cahyono; Heri Retnawati; Fitri Nur Mahmudah; Galeh Nur Indiatno Putra Pratama (Jurnal Pendidikan Vokasi, 2024)
Many studies report a significant relationship between self-control and academic achievement, although the strength of this relationship varies across studies. Moderator factors influencing this relationship remain unclear. Therefore, this meta-analysis aims to further explore the relationship between self-control and academic achievement and investigate potential moderating factors that may affect its strength. The study includes 70 samples from 16 primary studies published between 2005 and 2018. Data analysis was conducted using a random effects model with a significance level of Î± = 5%. In addition to the main analysis, six moderator variables were analyzed: education level, geographical region, self-control measurement tool, academic achievement measurement tool, and publication year. The results showed a moderate positive relationship between self-control and academic achievement (r = 0.32, p < 0.001). Moderator analysis indicated that all variables significantly influenced the strength of the relationship between self-control and academic performance. The positive relationship was stronger in studies with mixed participants and weakest among university students and stronger in studies conducted in the United States than in Africa and Europe. This study contributes meaningfully to the literature by clarifying moderator factors and providing insights for educators in designing targeted interventions to enhance academic performance through self-control development across diverse contexts.